An incomplete soft set and its application in MCDM problems with redundant and incomplete information - Xia, Sisi; Yang, Haoran; Chen, Kin (Zielona Góra: Uniwersytet Zielonogórski)
Multiple criteria decision making (MCDM) problems in practice may simultaneously contain both redundant and incomplete information and are difficult to solve. This paper proposes a new decision-making approach based on soft set theory to solve MCDM problems with redundant and incomplete information. Firstly, we give an incomplete soft set a precise definition. After that, the binary relationships of objects in an incomplete soft set are analyzed and some operations on it are provided. Next, some definitions regarding the incomplete soft decision system are also given.
Keywords: soft sets; incomplete soft sets; incomplete information; redundant information; multiple criteria decision making